Altered auditory processes pattern predicts cognitive decline in older adults: different modalities with aging - Yang, Junjie; Tang, Xiaochen; Lin, Shaohui; Jiang, Lijuan; Wei, Kai; Cao, Xinyi; Wan, Lingshan; Wang, Jijun; Ding, Hansheng; Li, Chunbo (Frontiers in Aging Neuroscience, 2023)
Background: Cohort studies have shown that older adults with hearing impairment as assessed by self-report or behavioural measures are at higher risk of developing dementia many years later. A fine-grained examination of auditory processing holds promise for more effective screening of older adults at risk of cognitive decline. The auditory mismatch negativity (MMN) measure enables one to gain insights into the neurobiological substrate of central auditory processing. We hypothesized that older adults showing compromised indexes of MMN at baseline would exhibit cognitive decline at the one-year follow-up. Methods: We performed cognitive evaluations with the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Form A and Form B) in 108 community-dwelling older adults and acquired EEG via the classic passive auditory oddball paradigm at baseline and 12-month follow-up.The results showed that young-old adults with future cognitive decline showed a decrease in MMN peak amplitude, accompanied by a forward-shifting latency, whereas in older adults it showed a delay in MMN latency, and unchanged MMN peak amplitude at midline electrodes(Fz, FCz and Cz). Furthermore, the peak amplitude of the MMN decreases with age in older adults aged 70-80 years rather than 60-70 years or >80 years. Conclusions: The altered MMN model exists in different aging stages and it's a promising electrophysiological predictor of cognitive decline in older adults. In addition, further research is needed to determine the neural mechanisms and potential implications of the accelerated decline in MMN in older adults.